Optimizing the Cleanliness Management of Coastal Lodgings and Homestays - Andi Ade Zulkifli (Journal La Bisecoman, 2023)
This study aims to determine the optimization of cleaners in providing cleaning services which so far is still based on the experience of managers when cleaning their own houses without being equipped with an understanding of the cleanliness standards of inns and homestays. This is feared to affect guest satisfaction while on Panrang Luhu Beach, so many visitors no longer want to return to the tourist attraction. This study focuses on the hygiene management standards of inns and homestays in the coastal area of Panrang Luhu, Bulukumba Regency and skills in cleaning inns and homestays on the coast of Panrang Luhu, Bulukumba Regency. The author refers to the descriptive research method, which is to provide an accurate picture of a phenomenon by collecting data and analyzing it descriptively, focusing on the hygiene management standards of inns and homestays in the coastal area of Panrang Luhu, Bulukumba Regency and skills in cleaning inns and homestays on the coast of Panrang Luhu, Bulukumba Regency.